A preliminary evaluation of synthetic cannabinoid use among adolescent cannabis users: Characteristics and treatment outcomes. (December 2016) - Blevins, Claire E.; Banes, Kelsey E.; Stephens, Robert S.; Walker, Denise D.; Roffman, Roger A.
Abstract: Little is known regarding the use of synthetic cannabinoids (SC), particularly use among adolescent substance users who may be at higher risk. The present exploratory study seeks to describe SC use and subjective effects among cannabis-using adolescents as well as compare the characteristics of cannabis users who do and do not use SC. Exploratory analyses evaluated cannabis treatment outcomes among SC users and non-users. Participants enrolled in a randomized, controlled intervention for cannabis-using high school students aged 14–19 ( N  = 252) completed questionnaires regarding their use of SC and other substances. Those who used SC in the past 60 days reported subjective effects of SC, consequences, and SC use disorder symptoms. Baseline characteristics, alcohol and other drug use, and treatment outcomes of SC users were compared to participants who never tried SC. Within this sample 29% had tried SC, and 6% used SC recently. Although most reported use at a relatively low rate, 43% of recent SC users reported SC use-disorder symptoms. Positive and negative subjective effects of SC were endorsed, with positive subjective effects reported more often. SC use was associated with more cannabis use, but not more alcohol or other (non-SC and non-cannabis) drug use. SC users did not differ from non-users on cannabis treatment outcomes. This exploratory study described SC use, and compared characteristics and treatment outcomes among SC users and non-users. Negative subjective effects of SC were reported as occurring less often, but SC use was associated with use disorder psychopathology. SC use was associated with more problematic cannabis use at baseline, but was not associated with use of other substances or differences in treatment outcome. Highlights: Heavy cannabis-using adolescents may be at increased risk of SC use. SC users report both positive SC subjective effects and adverse outcomes. SC users endorsed higher rates of cannabis use than SC nonusers. SC use was not associated with differential cannabis treatment outcomes. Rates of other psychoactive substance use did not vary by SC use.